Studi Hadis tentang Ziarah Pembersihan Makam - Novalia Azzahra; Dadah; Wahyudin Darmalaksana (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the grave pilgrimage. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the grave pilgrimage in the history of Ahmad No. 21937. The results and discussion of this study indicate that the status of the hadith has the quality of hasan li ghairihi with the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 21937 is relevant to be used as a base for grave pilgrimages to clean graves and remember death.